PENGGUNAAN UREA TABLET DAN KAPUR DOLOMIT TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PADI SAWAH PADA TANAH GAMBUT - Hercules Gultom; Mardaleni Mardaleni (UIR Press, 2013)
The purpose of this research was to know interaction effect of dolomit lime with tablet urea on peat land and recognize individually way antara dolomit lime and urea fertilizer. This research used the Completely Randomized Design for Factorial which consusted of two factors, namely dolomit factor (D) and tablet urea factor (U). The application of dolomit lime used dose: D0 = without dolomit lime, D1 = 5 g/plant, D2 = 10 g/plant and D3 = 15 g/plant. For tablet urea, the dose: U0 = without tablet urea, U1 = 2 tablets/plant, U2 = 4 tablets/plant, and U3 = 6 tablets/plant. The data were analyzed statistically with different test at the 5% significance level. The observed parameters were plant height, number of productive stem per plant, production per cluster, percentage of dried paddy, and dried paddy yield per ha. The results show that application of tablet urea with dolomit lime intereactionally had not different, but application tablet urea as well as dolomit lime partially had a difference. The best dose was 2 g/plan (U1) for tablet urea and 15 g/plant for dolomit lime. Furtehrmore, the best intereaction was D2U2 treatment.